Brain abscess mimicking acute stroke syndrome caused by dual Filifactor alocis and Porphyromonas gingivalis infections: A case report - Pruettichai Wisutep (2022)
This case report is about a woman who had a brain abscess in the left parietal lobe that atypically presented as acute stroke-like syndrome. Pus samples from brain abscess aspiration revealed the periodontal pathogens Porphyromonas gingivalis and Filifactor alocis. After dental health care and 8 weeks of combined antimicrobial therapy, the patient recovered completely.